A double-blinded, randomized, split-side, vehicle-controlled study of the efficacy of cleanser containing Acanthus ebracteatus Vahl., Suregada multiflora, and Acacia concinna in patients with atopic dermatitis: A pilot study - Winayanuwattikun, Waranaree; Varothai, Supenya; Tuchinda, Papapit; Kulthanan, Kanokvalai; Prasertworonun, Nuntida; Dasri, Phongphimon; Wanichthanarak, Kwanjeera; Akarasereenont, Pravit (Asian Pacific journal of allergy and immunology, 2023)
Barrier repair therapy is the key management approach for both eczematous and non-lesional skin of atopic dermatitis. The use of appropriate cleansers to enhance skin hydration is an adjunctive treatment that increases topical drug penetration. Anti-inflammatory properties of various medicinal plants in tropical Asia have been reported. Investigate the efficacy of herbal cleanser containing a combination of herbal extracts from Acanthus ebracteatus Vahl., Suregada multiflora, and Acacia concinna on seemingly intact skin in patients with atopic dermatitis by measuring improvements in the skin barrier function. This 2-week pilot study was a split-side, randomized, double-blinded, vehicle-controlled trial. All patients (n = 30) were asked to use both a cleanser with an active formulation containing the herbal extracts and a vehicle- controlled cleanser on each side of mid-volar forearm. Biophysical assessments including transepidermal water loss (TEWL), skin hydration, skin pH, and skin roughness were performed at baseline and upon study completion. Compared to baseline, the median percentage change in TEWL at the end of the study was significantly greater for the active side 10.4 (-19, 20.7) g/m2h than the control side -13.2 (-28.7, 9.1) g/m2h; p = 0.01. The median percentage change of skin hydration, skin pH, and skin roughness of the active side compared to the control side had no a statistical significance. This cleanser is beneficial when used as adjunctive therapy. Further studies should evaluate its anti- sinflammatory properties in the remedy or active phase of atopic dermatitis or other inflammatory skin diseases.